Electrochemically Activated Conductive Ni-Based MOFs for Non-enzymatic Sensors Toward Long-Term Glucose Monitoring - Chen, Yating; Tian, Yulan; Zhu, Ping; Du, Liping; Chen, Wei; Wu, Chunsheng (Frontiers in Chemistry, 2020)
Continuous intensive monitoring glucose is one of important approaches to recover the quality of lifespan of diabetic patients. One challenge for electrochemical enzymatic glucose sensor is its short lifespan for continuous glucose monitoring. Therefore, it is of great significance to develop non-enzymatic glucose sensor as an alternative approach for long-term glucose monitoring. This study presented a highly sensitive and selective electrochemical non-enzymatic glucose sensor using the electrochemical activated conductive Ni3(2,3,6,7,10,11-hexaiminotriphenylene)2 MOFs as sensing materials. The morphology and structure of MOFs were investigated by the scanning SEM and FTIR, respectively. The performance of the activated electrode towards the electrooxidation of glucose in alkaline solution was evaluated with cyclic voltammetry technology in the potential range from 0.2 V to 0.6 V. The electrochemical activated Ni-MOFs exhibited obvious anodic (0.46 V) and cathodic peaks (0.37 V) in the 0.1 M NaOH solution due to the Ni(II)/Ni(III) transfer. A linear relationship between the glucose concentrations (ranging from 0 mM to 10 mM) and anodic peak currents with R2=0.954 was obtained. It was found that the diffusion of glucose was the limiting step of the electrochemical reaction. The sensor exhibited good selectivity towards glucose in the presence of 10-folds uric acid and ascorbic acid. Moreover, this sensor showed good long-term stability for continuous glucose monitoring. Therefore, the good selectivity, good stability, and rapid response of this sensor suggest the promising prospects and potential applications in the non-enzymatic blood glucose monitoring for a long term.